2009
DOI: 10.1016/j.pmrj.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Locomotor Therapy Using Robotic‐Assisted Gait Training in Subacute Stroke Patients: A Randomized Controlled Trial

Abstract: Objective To evaluate the effectiveness of early and prolonged locomotor treatment with the use of a robotic‐assisted gait training (RAGT) device (Lokomat; Hocoma Inc., Zurich, Switzerland) on the functional outcomes of patients after subacute stroke. Design A nonblinded prospective, randomized, controlled study. Setting Rehabilitation department in tertiary university medical center. Patients Sixty‐seven patients in the first 3 months after subacute stroke were randomized into 2 groups as follows. Thirty‐seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 32 publications
7
129
1
1
Order By: Relevance
“…Walking training time in these studies varied from 20 to 60 min per session. Five studies were not included in the meta-analysis, because their quality was rated as poor (9,99,111), data were not available for the meta-analyses (99) or the data (93) were gathered from and analysed for the same group of subjects as that in the analysis (94) (tables I and SI 1 ).…”
Section: Specific Vs Traditional Walking Trainingmentioning
confidence: 99%
“…Walking training time in these studies varied from 20 to 60 min per session. Five studies were not included in the meta-analysis, because their quality was rated as poor (9,99,111), data were not available for the meta-analyses (99) or the data (93) were gathered from and analysed for the same group of subjects as that in the analysis (94) (tables I and SI 1 ).…”
Section: Specific Vs Traditional Walking Trainingmentioning
confidence: 99%
“…2 The decision to discharge patients from further therapy is often justified with a ''plateau'' in motor recovery. 3 However, further functional gains after acute rehabilitation are possible, even in the chronic stage.…”
Section: Introductionmentioning
confidence: 99%
“…There are different findings about robotic training in the literature. It is suggested that proof on the effectiveness of locomotor therapy is limited and it is not clear whether healing is greater compared with other gait rehabilitation methods (11)(12)(13)(14)(15)(16). Randomized controlled trials with larger, specific populations are needed to show effectiveness of robotic gait training in the different disorders such as HSP.…”
Section: Discussionmentioning
confidence: 99%